Prediction of the dynamic responses for two containerships operating in the black sea - Gasparotti, Carmen; Rusu, Liliana (Journal of Naval Architecture and Marine Engineering, 2014)
This work presents a methodology for the evaluation of the vessels operability in the basin of the Black Sea. The approach proposed is based on the results provided by a wave prediction system that was implemented and validated in the Black Sea. This offers a meaningful framework in the assessment of the seakeeping performance for ships operating in different conditions. The aim of the work is to improve the seakeeping performances for various types of ships that sail in the Romanian coastal zones. Two containerships are considered, of 1300TEU and 800TEU respectively, which have however the same displacement. For predicting the ship motions induced by the various wave conditions encountered in the operational area, it is necessary to know the transfer functions for different ship speeds and heading angles. These are computed with a numerical code based on the strip theory. The predicted motions are then compared with the limit values of the relevant seakeeping criteria, considered as the criteria for checking the operability of the ship. By defining the acceptable operating boundaries, the ship behavior in waves can be quantified. The vessel meets the criteria for those combinations wave height-wave period that are below the limit curves. The results are presented as operational maps for the Black Sea basin, allowing the identification of the areas that should be avoided due to unfavorable weather conditions. The methodology proposed herewith can be extended and applied to various marine environments and types of ships. DOI: http://dx.doi.org/10.3329/jname.v11i1.17289